Eksistensi Program Larasita Kaitannya Dengan Kepastian Hukum Dan Perlindungan Hukum Hak Atas Tanah (Studi di Kantor Pertanahan Kota Medan) - Muhammad Haris; Masitah Pohan; Ruslan Ruslan (SOSEK : Jurnal Sosial dan Ekonomi, 2021)
Land registration activities through the Larasita Program in Medan City began in 2009 with the aim that access related to legal certainty of land rights, especially for small communities or economically weak people, receive the same treatment and status as those with more economical communities. The problem in this research is the legal arrangement of Larasita in relation to legal certainty and legal protection of land rights. Implementation of the Larasita program by the Medan City Land Office. Constraints faced by the Medan City Land Office in implementing the Larasita program and the solutions made to overcome these obstacles. This research uses an empirical juridical approach. A juridical approach is used to analyze various laws and regulations related to the existence of the Larasita Program (People's Service for Land Certification). Meanwhile, the empirical approach is used to analyze the law which is seen as the behavior of landowners that is patterned in people's lives, who always interact and relate in social aspects. This research uses data collection tools in the form of literature study / document study and interviews. To obtain primary data, interviews were conducted with 2 (two) Medan City Land Office employees (informants), and 2 (two) land owners (respondents). Analyzed using qualitative analysis techniques. The results of the discussion that Larasita legal arrangements are related to legal certainty and legal protection of land rights as regulated in Perkaban No. 18 of 2009 concerning Larasita was built and developed to realize the mandate of Article 33 paragraph (3) of the 1945 Constitution, Law number 5 of 1960 concerning Basic Agrarian Principles, Government Regulation Number 24 concerning Land Registration, Regulation of the Minister of Agrarian Affairs Number 3 Years 1997 concerning Implementing Provisions Government regulation number 24 of 1997 concerning land registration. Legal certainty and legal protection of land rights through the Larasita program has been realized by carrying out land registration and has been achieved by the issuance of a valid proof letter as a strong evidence tool in the form of a certificate as regulated in Government Regulation Number 24 of 1997.The implementation of land registration activities through the Larasita program at the Medan City Land Office has been carried out according to procedures based on the provisions of the prevailing laws and regulations. The existence of the Larasita program after the emergence of the Complete Systematic Land Registration Program (PTSL). The obstacles faced by the Medan City Land Office in implementing the Larasita program, namely internal factors consisting of the lack of budget for Larasita activities. Use of Larasita Vehicles for other activities. Difficulties in Making Schedule for Larasita visits, and Difficulties in Site Selection. External obstacles, among others, the internet network which is often disconnected. Infrastructure conditions that are difficult to reach. Lack of public knowledge. Lack of socialization. Internal solutions are carried out such as increasing the Larasita Budget. external solutions do outreach. Bring files and input data at the Medan City Land Office